Evaluating the sense of presence in non immersive virtual environment - Norehan, bte Zulkiply (Universiti Malaysia Sarawak (UNIMAS), 2001)
A primary argument for the efficacy of Virtual Environments (VE) applications is that the user is "present" in the simulated environment. Previous research showed that there is a strong relationship between presence and the level of task performance in the VE. Although, the concept of presence is widely discussed, but there is relatively little research conducted to evaluate the sense of presence in the VE with n::spe ct to non-immersive virtual environment. The wide usage of desktop vinual environment recently inspire the move to evaluate Ihe sense of presence in non immersive VE. in general, presence is defined as the subjective experience of being in one environment (there) when one is physically in another environment (here). Based on previous research, the amount of presence experienced by user of a virtual environment is determined by two form of faclors, namely contributing factors and distraclion factors, which may enhanced or interfered Ihe sensation of" being there" in the virtual environment". In respect to those factors, a Present Ouestionnaire (PO) is developed to idenlify and measure the degree to which aspects of the virtual environment engendered a sense of presence. The results of an administralion of the questionnaire in conjunclion wilh an experiment on Ihe performance of basic tasks in VE are presented. Results indicate there is positive probability of tendency of experiencing presence in the virtual environment used. An analysis of the feedback provided by the chosen subjects has revealed a number of factors that could affecllhe sense of presence in such VE system.